Resistence and gender in the archives of the Cone Sul military dictatorships (Tempo e Argumento, 2013)
This article presents a reflection on the archives that hold collections on dictatorships in the countries of the so called Cone Sul (Argentina, Bolivia, Brazil, Chile, Paraguay and Uruguay) which have been explored in the Project Gender, Feminisms and Dictatorships by the Laboratory for the Study of Gender and History of the Federal University of Santa Catarina. It aims to show how one can find gender perspectives in collections that originally had as their main purpose the repression against political movements of resistance to dictatorships, or that were constituted precisely in the memory effort of this resistance, but that did not problematized particularly gender issues. The reflection is intended to show that gender is an important aspect in the constitution of resistance discourses in these countries.
Keywords: gender; dictatorship; Cone Sul; archives; memory; archives - history